Concrete failure simulation method based on discrete element method. (September 2022) - Huang, Pingming; Pan, Xupeng; Niu, Yanwei; Du, Longji
Highlights: A high-efficiency calibrating method of meso-parameters in PFC have been improved. The complete process of crack initiation, propagation and coalescence have been simulated DEM. Four-point bending strength test and direct shear strength test has been carried out by DEM. Abstract: This paper improves the method of high-efficiency calibrating the meso-parameters considering the concrete aggregate gradation, and carries out numerical simulations of four-point bending strength test and direct shear strength test on concrete beams. Firstly, unconfined uniaxial compression test carried out to calibrate the meso-parameters of C40 concrete based on DEM. Secondly, the accuracy of the numerical model is verified according to the stress-strain curve and failure morphology of concrete prism. Finally, the crack propagation and load-displacement curves of concrete beams under four-point bending strength test and direct shear strength test were analyzed. The result show as follow: ① The DEM numerical model which take into account the concrete as a three-phase composite material can well realize the mechanical property of concrete. The display of force chains and micro-cracks greatly contributes to the concrete failure mechanism. ② The numerical model is generated by the random distribution of particles, which shows the characteristics of concrete heterogeneity, and defines the contact model between particles with parallel bond model (PBM). Compared with the numerical simulation and experiment results, the error is within 10.4%; ③ In four-point bending strength test, the crack initiates from the bottom edge of the beam and propagates upward. With the increase and coalescence of micro-cracks, only one concentrated, wide and long macro-crack is formed; In direct shear strength test, however, the high shear stress of two shear surfaces resulted in the generation of cracks. With the one side crack coalescence, the other side of crack initiate follow, and finally two coalescence macro-cracks are formed.